Volunteerism as an Agent of Transformation (LEARNing Landscapes, 2012)
I once believed that everything I knew about learning and teaching was the result of being a student and a teacher in schools and universities. But that was learning and teaching for a specific purpose and audience, structured for the here and now, in formal, familiar, comfortable settings with people who shared common experiences and interests. Since 2003 I have been volunteering and working with youth and educators in developing and post-conflict countries including Palestine, Nigeria, and Kenya. However, it is only within the last few years that I have come to realize that my volunteerism has provided me with informal learning opportunities that have led me to better understand who I am as a person, educator, and learner.
Keywords: learning; teaching; volunteering; informal learning